Análise dos processos de certificação ISO 14001 e as repercussões nas competências gerenciais e profissionais em empresas de transporte rodoviário - Balliana Jr, Gildo (2013)
Brazil has experienced significant changes after the economic openness in the early 90. Brazilian companies under the major impact of foreign products suffered the pressure to change their plans and methods of production and control. They used the certification processes as a strategy to meet the new requirements imposed by the national and international market. The road freight transport is the main mode of transferring and moving goods within the country. It is a segment of great importance to the national economy, considering its functions: economic (connect industry and trade) and social (integrate Brazilian regions). However, the activity causes pollution and requires management to reduce environmental impacts. This research aims to establish a relationship between the variables: environmental management and professional skills. In order to achieve this objective the processes of ISO 14001 environmental certification in freight transportation companies was analyzed, as well as the resulting changes in management skills. The methodological procedures for data collection were visits to companies, interviews with professionals in strategic, tactical and operational sectors, document analysis, web pages analysis and researcher’s observations. The research is relevant considering the small number of academic studies that describe road freight transport companies. The survey displays the environmental and management behavior of the segment, therefore contributing to a better understanding of the activity. The results indicate that the organizations surveyed did not change their skills after the implementation of ISO 14001. One reason for this is that management skills have been developed over the years, and have already been assimilated internally, thus implementation of new environmental standards did not change the management dynamics.